FK506 and Its Analogs - Therapeutic Potential for Neurological Disorders - Klettner, A.; Herdegen, T. (Current Drug Targets-CNS & Neurological Disorders, 2003)
Immunophilin ligands such as FK506 and Cyclosporin A, used in immunosuppression, are wellcharacterized drugs. In the past, they had been the center of attention as a putative therapeutic strategy for neuroregeneration and neuroprotection. In contrast to Cyclosporin A, FK506 readily crosses the brain-bloodbarrier and, thus together with its derivatives, may represent a novel approach to the treatment of neurological disorders.FK506 exerts profound neuroprotective and neuroregenerative effects in vivo and in vitro. The mechanism underlying neuroregeneration is fairly well understood. It is independent of the inhibition of calcineurin, which is responsible for the immunosuppression, but operates via the binding of FKBP52 and the heat shock protein (Hsp) 90. In contrast, the underlying pathways of neuroprotection are far less understood. Protection is apparently independent of calcineurin, as shown by non-calcineurin inhibiting derivatives, such as V-10,367 and GPI-1046, but the intracellular actions remain to be defined. FK506 has been shown to interfere with the apoptotic pathway of neuronal cells, including inhibiting JNK activity, cytochrome c release, caspase 3 activation, and CD95 ligand expression. These effects are in part mediated by the inhibition of calcineurin and may not contribute to protection. Our recent studies suggest that the protective properties of FK506 and its non-calcineurin inhibiting derivatives are realized by a fast induction of heat shock proteins. The induction of the heat shock response by immunophilin ligands might prove to be an interesting target for neuroregeneration and neuroprotection.
Keywords: neuroprotection